Far-infrared line deficits in galaxies with extreme LFIR/M H2 ratios - Graciá-Carpio, J; Sturm, E; Hailey-Dunsheath, S; Fischer, J; Contursi, A; Poglitsch, A; Genzel, R; González-Alfonso, E; Sternberg, A; Verma, A; Christopher, N; Davies, R; et al. (2011)
We report initial results from the far-infrared fine structure line observations of a sample of 44 local starbursts, Seyfert galaxies, and infrared luminous galaxies obtained with the PACS spectrometer on board Herschel. We show that the ratio between the far-infrared luminosity and the molecular gas mass, LFIR/MH2, is a much better proxy for the relative brightness of the far-infrared lines than LFIR alone. Galaxies with high LFIR/MH2 ratios tend to have weaker fine structure lines relative to their far-infrared continuum than galaxies with LFIR/MH2 ≲ 80 L ⊙ M⊙-1. A deficit of the [C II] 158 μm line relative to LFIR was previously found with the Infrared Space Observatory, but now we show for the first time that this is a general aspect of all far-infrared fine structure lines, regardless of their origin in the ionized or neutral phase of the interstellar medium. The L FIR/MH2 value where these line deficits start to manifest is similar to the limit that separates between the two modes of star formation recently found in galaxies on the basis of studies of their gas-star formation relations. Our finding that the properties of the interstellar medium are also significantly different in these regimes provides independent support for the different star-forming relations in normal disk galaxies and major merger systems. We use the spectral synthesis code Cloudy to model the emission of the lines. The expected increase of the ionization parameter with L FIR/MH2 can simultaneously explain the line deficits in the [C II], [N II], and [O I] lines. © 2011. The American Astronomical Society. All rights reserved. Printed in the U.S.A.